Strategic self-talk for anxiety regulation: competition time - Hatzigeorgiadis, A.; Proskinitopoulos, T.; Tzormpatzakis, E.; Mylonopoulos, A.; Galanis, E. (28th Annual Congress of the European College of Sport Science, 4-7 July 2023, Paris, France, 2023)
Self-talk interventions have proven effective in lowering anxiety levels in young athletes in field experiments, however, such experiments cannot resemble real competitive conditions. The purpose of the present study was to explore the effects of a strategic self-talk intervention on pre-competition anxiety and self-confidence in young swimmers. Fifty-five competitive swimmers initially agreed to participate in the study. Eventually, 38 (22 females) with a mean age of 14.72, training on average 5.86 times per week for an average of 14.02 hours, completed the requirements of the study. Swimmers competed in two qualifying for the national championship competitions that took place at an 8-week interval. Hence, the self-talk intervention was implemented over the 8-week period in-between these competitions. During this period, participants of the experimental group received a tailor-made intervention based on an opening need assessment session. The purpose of the intervention was to assist swimmers to develop specific self-talk plans for the competition but also to change unproductive self-talk. The importance of the competition was assessed one day before the competition, whereas pre-competition anxiety and self-confidence were assessed approximately 15 minutes before the start of each swimmer`s main race. Preliminary analyses showed no differences in baseline anxiety and self-confidence between the intervention and the control groups; in addition, no between or within-group differences were recorded for competition importance. Two-way (2x2) mixed model MANOVA showed a significant multivariate group by time interaction, F(3, 34)= 3.00, p< .05, partial *2= .21. Examination of the pairwise comparisons revealed that for the intervention group cognitive and somatic anxiety were reduced and self-confidence was increased, whereas no significant differences were recorded for the control group. The findings of this pragmatic intervention study may lack the methodological rigor of controlled lab experiments due to the dynamic and unpredicted competitive environment, however, they hold important ecological validity, thus complementing previous findings from field experiments.